The yuan's exchange rates and pass-through effects on the prices of Japanese and US imports - Yuqing Xing (Asian Development Bank Institute (ADBI), 2010)
This paper estimated the pass-through effects of yuan's exchange rates on prices of the US and Japanese imports from the People's Republic of China (PRC). Empirical results show that, a 1% nominal appreciation of the yuan would result in a 0.23% increase in prices of the US imports in the short run and 0.47% in the long run. Japanese import prices were relatively more responsive to changes of the bilateral exchange rates between the yuan and the yen. For a 1% nominal appreciation of the yuan against the yen, Japanese import prices would be expected to rise 0.55% in the short run and 0.99%, a complete pass-through, in the long run. The high degree of pass-through effects were also found at the disaggregated sectoral level: food, raw materials, apparel, manufacturing, and machinery. However, further analysis indicated that the high pass-through effects in the case of Japan were mainly attributed to the PRC's policy to peg the yuan to the United States (US) dollar, and that the dollar is used as a dominant invoicing currency for the PRC's exports to Japan. After controlling the currency invoicing factor, I found no evidence that the yuan's cumulative appreciation since July 2005 was passed on to prices of Japanese imports at either the aggregate or disaggregated levels. The estimated low pass-through effects of the yuan's appreciation suggest that a moderate appreciation of the yuan would have very little impact on the PRC's trade surplus.
Keywords: F31; F32; 330; Währung; Renminbi; Exchange Rate Pass-Through; Import; Chinesisch; Außenhandelspreis; Japan; USA